Which risk‐adjustment index performs better in predicting 30‐day mortality? A systematic review and meta‐analysis. Issue 2 (6th February 2015) - Yang, Mo; Mehta, Hemalkumar B.; Bali, Vishal; Gupta, Parul; Wang, Xin; Johnson, Michael L.; Aparasu, Rajender R.
Abstract: Rationale, aims and objectives: Individual comparisons of the performance of risk‐adjustment indices have been widely conducted. Few reviews have been conducted to summarize the performance of different risk‐adjustment indices. A 30‐day mortality rate is widely used to evaluate the quality of care in hospitals by federal agencies like the Centers for Medicare and Medicaid Services. This study examined relative performance of risk‐adjustment indices that predict 30‐day mortality. Methods: Databases including Medline, PubMed and PsycINFO were searched for studies that compared risk‐adjustment indices. The search protocol included comparative studies in which the performance of risk‐adjustment indices were compared across any defined cohort to compare 30‐day mortality, including mortality within 30 days and intensive care unit mortality, which lasts less than 30 days. Data were extracted using a structured form and abstract data included author and publication year, population studied (including location, sample size, study time period), comparison indices, outcome studied, results and conclusions from the results. A meta‐analytical approach was used to summarize all the studies. Scaled ranking score was used to estimate the relative superiority of any given risk‐adjustment indices. A hypergeometric test was carried out to evaluate the performance of risk‐adjustment measures. Results: Out of 2805 studies identified, 23 studies met the eligibility criteria. Main risk‐adjustment indices used for comparison included Acute Physiology and Chronic Health Evaluation, Sequential Organ Failure Assessment score, Charlson co‐morbidity index, Model for End‐Stage Liver Disease score and Simplified Acute Physiology Score (SAPS). Based on scaled ranking score, SAPS performed best (score 0.510) among all the risk‐adjustment indices. However, based on hypergeometric test, the five measures performed equally well. Conclusions: Although all the selected risk‐adjustment indices perform equally well, SAPS seems better than other indices for short‐term mortality based on scaled ranking score.